Inventing and validation of a new family scale; Asian family characteristics scale/skala ciri kekeluargaan asia - Musa, Ramli (2014)
Introduction; Research in the field of family study in Malaysia is facing a setback as there is no validated instrument to explore the family environment. The intensifying social related problems such as illegal racing, substance misuses, conduct disorder, physical and sexual abuse, indicate that exploration on family environment is essential. The idea to invent a new scale was triggered based on poor outcomes of previous research project “Translation and Validation of the Family Environment Scale (FES) Questionnaire” which was funded by Ministry of Health Malaysia (HKL/98/CRC/ER/180/07) [Publication; Khairani & Ramli M et al]. The results of this project show that direct translation and adopting of western questionnaire is not always feasible as Asian family values are different.